If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + 2bx + ay + 2by = 0 Reorder the terms: ax + ay + 2bx + 2by = 0 Solving ax + ay + 2bx + 2by = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2bx' to each side of the equation. ax + ay + 2bx + -2bx + 2by = 0 + -2bx Combine like terms: 2bx + -2bx = 0 ax + ay + 0 + 2by = 0 + -2bx ax + ay + 2by = 0 + -2bx Remove the zero: ax + ay + 2by = -2bx Add '-2by' to each side of the equation. ax + ay + 2by + -2by = -2bx + -2by Combine like terms: 2by + -2by = 0 ax + ay + 0 = -2bx + -2by ax + ay = -2bx + -2by Reorder the terms: ax + ay + 2bx + 2by = -2bx + 2bx + -2by + 2by Combine like terms: -2bx + 2bx = 0 ax + ay + 2bx + 2by = 0 + -2by + 2by ax + ay + 2bx + 2by = -2by + 2by Combine like terms: -2by + 2by = 0 ax + ay + 2bx + 2by = 0 The solution to this equation could not be determined.
| 6-9y=16-3y | | 2.6x+17=-9 | | -(3-x)+4=20 | | 75.89+0.12t=0.36t+27.41 | | 13=-4+z | | c-4=-3*b+a*c | | 7x+x=128 | | 10a-4b=9 | | 3(x-4)+24-3x=12 | | -10+9(4v-5)= | | -3*b+a*c=c-4 | | 2=ln(x+7) | | -3n+1=-3n+6 | | 12-4m=-3+m | | -2t-7t-3=12 | | a^3-8a^2+15a= | | 9a+2ab+a-ba-4a= | | (4+3i)-(7-2i)=0 | | -2(x+6)=3x-8 | | H(x)=40 | | -2(y-4)=3y-2 | | 2x-12=3x-8 | | (x-10)(x+10)=100 | | 5x-3x+2=8x-4 | | 6x-48=5x | | 5=x+3-(3x) | | -27=4x-17 | | -(8x-4)-(5x-6)+7=-12(x-1)-(4x+13)+3 | | 40=2x^2-6x | | 2y-4+16=5y-9 | | 12b+6(3-b)=b+3 | | -5=2x^2-6x |